Viscosity reduction of heavy crude oil through the addition of nanofluids on the non-thermal process (2017)
The growth of the world population, the constant industrialization of developed countries and a considerable increase in energy consumption have promoted an increasing demand for oil in the world. However, the decline in light crude reserves makes it attractive to exploit heavy and extra-heavy oil to meet energy requirements due to recoverable oil capacity (IEA). Heavy and extra-heavy crude (bitumen) is defined as one with API gravity equal to or less than 20 and equal to or less than 10 (denser than water), respectively. Despite the importance and high volumes of heavy crude reserves, development, production and refinement is difficult due to its physico-chemical properties, mainly its high density and viscosity, low API gravity, and high hydrocarbon content Heavy crude (HO) and extra-heavy (EHO) crude oils usually have a large percentage of heavy components such as resins and asphaltenes which reduce API gravity and drastically increase crude viscosity. In order to improve the transportation of heavy crude oil to the surface, the conventional techniques used are heating piping and pumping stations, dilution with less viscous solvents, emulsification, and reduction of friction (annular flow). However, these techniques are costly due mainly to the high consumption of raw material, the heating of large pipe distances and the need for additional processes for the transport of crude oil. For this reason, this thesis is presented with the objective of analyzing a new technology that allows improving the transportation of heavy crude oil to reservoir and surface conditions through the application of nanofluids in non-thermal processes. It is expected to be a novel technique and competitive in economic terms since nanofluid is obtained by means of little complex synthesis routes and its quantity of use in comparison with the conventional solvents is much smaller.